Rental prices in Germany: A comparison between migrants and natives. (15th February 2021) - Eilers, Lea; Paloyo, Alfredo R.; Vance, Colin
Abstract: This paper deals with the question of whether migrants pay a rent premium for apartments of comparable quality and neighborhood characteristics. We use a two‐step selection‐correction model augmented by a control function to account for nonrandom neighborhood choice. The estimation sample is a uniquely assembled panel comprising the Socio‐Economic Panel (SOEP), information on household and apartment characteristics, as well as georeferenced data describing neighborhood quality. Our estimates reveal that people with migration backgrounds are not penalized in the German local rental market in terms of higher rental payments.